Teores de carotenoides e expressão gênica durante o amadurecimento do mamão papaia e sua relação com a capacidade antioxidante - Martins, Gabriela Ferreira [UNIFESP] (2014)
Papaya (Carica papaya L.) is a tropical fruit widely consumed worldwide and has a high antioxidant capacity due to the presence of bioactive compounds such as polyphenols and carotenoids . This study aimed: 1) determine the levels of carotenoids and phenolic compounds of two papaya cultivars widely consumed in Brazil, 'Golden' and 'Sunrise', in three stages of ripeness: green, intermediate and mature; 2) Identify the carotenoids of the two samples of papaya cultivars in the three stages of ripeness; 3) Establish the expression of key genes related to synthesis of carotenoids; 4) evaluate the antioxidant capacity in vitro samples of papaya and correlate with the levels of carotenoids and polyphenols of the two cultivars in the three stages of ripeness. There was an increased in the phenolic content in both cultivars throughout the three stages of ripening - 17.68 to 23.67 mg EAG/100g in ' Golden' and 16.54 to 26.92 mg EAG/100g in ' Golden ' - as well as antioxidant activity, verified by the ABTS method - 9.92 to 15.93 micromol trolox / g in' Golden ' and 16.81 to 22.26 micromol trolox / g in ?Sunrise?. However, there was no effect of ripening on the antioxidant activity quantified by the ORAC method and lipophilic peroxyl in both cultivars. The main carotenoids identified in the two cultivars were all-trans ? lycopene, all- trans - ? - cryptoxanthin and all- trans - ? -carotene, whose levels rose during ripening. The content of total carotenoids increased from 3.17 to 7.34 mg / g fresh weight and 1.85 to 10.13 mg / g fresh weight in ' Golden' and ' Sunrise?, respectively. The gene expression related to the synthesis of carotenoids also was verified, with decreased expression of genes involved in the biosynthesis of lycopene - Psy, Pds and Zds and increased gene expression of ? - carotene cyclase - Lcy?, related to the increase in levels of ? -carotene in both cultivars. Since the gene ? - carotene hydroxylase, ?-ch, showed increased only in the regulation cultivar Golden?, while the levels of alltrans ?-cryptoxanthin have been high in ?Golden? and "Sunrise" during ripening. Throughout ripening, we observed an increase in levels of bioactive compounds, carotenoids and phenolics, on the two cultivars, although only antioxidant capacity against ABTS radical has risen over the stages of maturation.